Development of Performance Assessment Instruments Through Practical Learning to Improve Science Process Skills - Elfrida Elfrida; Nursamsu Nursamsu; Raja Novi Ariska (Postgraduate, University of Mataram, 2021)
Basic Biology subjects are integrated between theory and practicum. Practical learning is an essential way that teachers can take to improve students' science process skills, so a valid instrument is needed to measure it. The objective of this study is to produce a valid performance assessment instrument in practical learning; a student worksheet in practical learning; the improvement of science process skills; and teacher response. The type of research is referring to model of 4-D. The subject of research is composed of the students in the odd semester academic year 2021-2022 at SMA Muhammadiyah Langsa. Instruments of research consist of validation sheet, student worksheet, observation sheet, questionnaire. The findings show validity score is 84% (good category); student worksheet in practical learning is 43% (very good category); there is the improvement of students science process skills before and after the practical learning, which shows by N-gain value of 0.64% (high category); and teacher response to developed performance assessment instrument is 83% (very practical category).